Delayed Gel Indurations as an Adverse Effect of Polyacrylamide Filler and Its Easy Treatment. (9th October 2012) - Kavoussi, Hossein; Ebrahimi, Ali
Abstract : Background . The more increasing use of permanent soft tissue fillers such as polyacrylamide hydrogel (PAAG) for aesthetic purposes, the more adverse events resulting from them are reported. Occasionally, nonserious complications and misdiagnosis result in unnecessary surgeries and sequels. Objective . To introduce delayed gel indurations (DGIs) as a late onset complication of PAAG and its easy treatment. Patient and Methods . Twenty patients (17 females and 3 males) referred to us with subcutaneous mass at injected site of PAAG. We diagnosed DGI based on clinical and sonography findings and treatment was performed with a hole by 16-gauge needle and squeezing. Results . From 20 patients with 21 cases of DGI, 5 (23.8%), 5 (23.8%), and 5 (23.8%) cases in cheeks, glabella, and lips were seen, respectively. The time range between PAAG injection and presentation of patients was 10–28 months (mean = 17.5%). All of the patients responded very well to treatment without recurrence and any complications. Conclusion . DGI is a nonserious, late onset, and easily treated complication of PAAG that is probably induced due to water exchange between gel and surrounding tissue and modest host immune reaction to gel.